Russian Provincial Church Mural Painting of the 19th Century in the Art History - Pavlova, Anna L. (Actual Problems of Theory and History of Art, 2022)
The keynote task of this paper is to make it clear why and how the scholars’ views on the monumental painting in the Central Russia churches of the 19th century have been changing.As early as in 1840s, the mural painting of the provinces attracted researchers’ attention of that time and almost at the same time was badly criticized by them. The monumental painting was blamed of being secondary in respect to the Western European art meaning that the use of engravings as the patterns proved the lack of independent and original approach. The church mural painting of the Russian provinces was not included in the mainstream art history and fell out of the scholars’ sphere of interest for almost a century.Nevertheless, from the study of the problem it becomes clear that the interest in the mural painting has always remained keen on the periphery of the metropolitan art criticism. In parallel with the metropolitan study of art, a provincial one developed that was devoted to the local pieces of art analysis. Beginning the end of the 1980s, the number of publications about church paintings started to gradually increase stimulated by the emerging interest in the late icon-painting. It grew lately evident that the negative critical views at large were expressed through the ignorance of the mural painting monuments. The key point in the changing of attitude about them is the publication and interpretation of documents from regional archives carried out by the local scholars mainly.
Keywords: study of art in the Provinces; church mural painting of 19th century; Russian art history; provincial painters